Technology adoption decisions in the household: A seven‐model comparison. (2nd December 2014) - Brown, Susan A.; Venkatesh, Viswanath; Hoehle, Hartmut
<x xml:space="preserve">Abstract</x> We identified 7 theoretical models that have been used to explain technology adoption and use. We then examined the boundary conditions of these models of technology adoption when applied to the household context using longitudinal empirical data from households regarding their purchase and use decisions related to household technologies. We conducted 2 studies and collected 1, 247 responses from U.S. households for the first study and 2, 064 responses from U.S. households for the second study. Those households that had adopted household technologies were surveyed regarding their use behavior. Potential adopters (i.e., those who had currently not adopted) were surveyed regarding their purchase intentions. This allowed us to identify the most influential factors affecting a household's decision to adopt and use technologies. The results show that the model of adoption of technology in the household provided the richest explanation and explained best why households purchase and use technologies.